The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.15252/embj.2019103009
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine deprivation alters the origin and function of cancer cell exosomes

Abstract: Exosomes are secreted extracellular vesicles carrying diverse molecular cargos, which can modulate recipient cell behaviour. They are thought to derive from intraluminal vesicles formed in late endosomal multivesicular bodies ( MVB s). An alternate exosome formation mechanism, which is conserved from fly to human, is described here, with exosomes carrying unique cargos, including the GTP ase Rab11, generated in Rab11‐positive recycling endosomal MVB … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
139
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(166 citation statements)
references
References 80 publications
6
139
0
1
Order By: Relevance
“…Tumour-derived EVs support broad oncogenic processes such as angiogenesis [10] , immune modulation [ 11 , 12 ], and metastasis [13] , [14] , [15] , [16] , [17] . Compared to non-malignant cells, cancer cells have been found to increase the amount of EVs produced [18] , [19] , [20] , shift the subtype of EVs that they secrete [21] , and/or alter the cargo molecules that are selected for expulsion [ 2 , 22 , 23 ]. Of note, education by tumor cells can also affect the secretion rate and the content of EVs derived from platelets [24] , as well as noncancer cells in the TME [8] , but in this review we chose to focus on EV secretion from cancer cells only.…”
Section: Oncogenes and Tumor Suppressors Governing Ev Secretionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumour-derived EVs support broad oncogenic processes such as angiogenesis [10] , immune modulation [ 11 , 12 ], and metastasis [13] , [14] , [15] , [16] , [17] . Compared to non-malignant cells, cancer cells have been found to increase the amount of EVs produced [18] , [19] , [20] , shift the subtype of EVs that they secrete [21] , and/or alter the cargo molecules that are selected for expulsion [ 2 , 22 , 23 ]. Of note, education by tumor cells can also affect the secretion rate and the content of EVs derived from platelets [24] , as well as noncancer cells in the TME [8] , but in this review we chose to focus on EV secretion from cancer cells only.…”
Section: Oncogenes and Tumor Suppressors Governing Ev Secretionmentioning
confidence: 99%
“…Besides this tumor intrinsic link between metabolism and EV secretion, extrinsic changes in cancer cell metabolism can also influence the production of cancer EVs. A recent publication reported that the depletion of glutamine from the TME causes a shift in the subtype of cancer EVs that are released; switching from late-endosomal CD63-positive exosomes towards RAB11a-positive exosomes that originate from recycling endosomes and promote tumor vascularization [21] .…”
Section: Tumor Characteristics Linked To Ev Upregulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, using Drosophila model and human cell lines, Fan et al (2020) have found that glutamine depletion induces secretion of exosomes carrying exclusive cargos created in Rab11−positive recycling endosomal MVBs. Interestingly, the release of exosomes from glutamine depleted HCT116 cells stimulate angiogenesis and enhances tumor cell proliferation.…”
Section: Autophagy and Exosomes Relationship In Cancermentioning
confidence: 99%
“…A recent article by Fan et al () clearly illustrates the power of such cell biology approaches. In this work, the authors now demonstrate an additional complexity of EVs formed intracellularly in endosomes, by showing that exosomes can contain the usual late endosomal compartments such as the tetraspanin CD63 and the Rab7 intracellular trafficking GTPase, but also molecular actors of earlier endosomal compartment such as Rab11a that decorates recycling endosomes.…”
Section: Potential Switch Of Exosome Biogenesis Pathways During Glutamentioning
confidence: 99%